2022
DOI: 10.12821/ijispm050401
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of business intelligence in public hospitals

Abstract: In this paper, DeLone and McLean's information systems success model is empirically tested on 12 public hospitals in Denmark. The study aims to investigate the factors that contribute to business intelligence (BI) success. 1,352 BI endusers answered the questionnaire. A partial least square structural equation model was used to empirically test the model. We find that system quality is positively and significantly associated with use and user satisfaction, and that information quality is positively and signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
2
18
1
1
Order By: Relevance
“…In like manner, Nelson et al (2005) found that BI system quality in terms of response time, accessibility, flexibility and integration positively and statistically affect user satisfaction. The same result was obtained by the model of Gaardboe et al (2017), which found a significant correlation between system quality and user satisfaction of BI. Hence, we hypothesize:…”
Section: System Qualitysupporting
confidence: 83%
See 3 more Smart Citations
“…In like manner, Nelson et al (2005) found that BI system quality in terms of response time, accessibility, flexibility and integration positively and statistically affect user satisfaction. The same result was obtained by the model of Gaardboe et al (2017), which found a significant correlation between system quality and user satisfaction of BI. Hence, we hypothesize:…”
Section: System Qualitysupporting
confidence: 83%
“…In like manner, Gonzales and Wareham (2019) also used the same model to explore the influence of information, system and service quality on system usage, satisfaction and then individual benefits as determinant factors of BI success. In addition, Gaardboe et al (2017) found the effect of quality dimensions on satisfaction and individual performance are vital factors in BI efficiency among Danish public hospitals. Overall, the above research confirms the validation and reliability of the DMM to measure the BI effectiveness from the user benefits viewpoint, not the organizational benefits.…”
Section: Literature and Theoretical Basismentioning
confidence: 99%
See 2 more Smart Citations
“…It is highly important for organizations to be able to recognize and exploit relevant and important information among enormous amount of data generated in business world each day. Only if BI is used to enhance decision making [4] or to improve business processes [5], it can affect the organization's performance. Therefore, BI can be an important means of competitive advantage for the company, if properly applied and utilized.…”
Section: Introductionmentioning
confidence: 99%